PENGARUH PEMAHAMAN MITIGASI BENCANA GEMPA BUMI DAN KONSEP DIRI TERHADAP KESIAPSIAGAAN BENCANA - Setianti, Ning (JURNAL TECHLINK, 2023)
Indonesia is a country encircled by the Pacific ring of fire, so it has a high potential for natural disasters, especially earthquakes. Responses to efforts to provide information and increase students' understanding of natural disasters and mitigation have been carried out through the world of education. The aim of the study was to identify and analyze the effect of understanding earthquake disaster mitigation and self-concept on disaster preparedness. This type of quantitative research with data collection methods in the form of questionnaires. The time of the research was carried out from September to December 2022. The research location was at SMAN 5 Depok. The results of the study show that there is a partial and simultaneous effect of understanding earthquake disaster mitigation and self-concept on disaster preparedness in class XI students of SMA N 5 Depok, West Java. This means that the more understanding of earthquake disaster mitigation and self-concept increases, the more disaster preparedness the students will have. A greater influence on student disaster preparedness is self-concept. The research recommendation is the need for continuous learning about earthquake disaster mitigation and self-concept towards disaster preparedness in students. This aims to increase student understanding regarding natural disaster mitigation.